GENERAL PROGRAMME OF THE IMPLEMENTATION OF NAIADES IN THE SLOVAK REPUBLIC - THE STATUS QUO AND NECESSARY MEASURES FOR LOGISTICS AND NAUTICAL PERSONEL - David, Andrej; Lednicky, Martin (Doprava a spoje, 2010)
This article consists of the SWOT analysis of the education system of the Slovak Republic in the field of inland water transport, its advantages and disadvantages and the measures addressed to nautical and logistics personnel which follow from the General Programme of the Implementation of NAIAEDS in the Slovak Republic (the Slovak NAP).